Analisis Yuridis Pembelisan Dalam Perkawinan Adat Suku Kodi Kabupaten Sumba Barat Daya - Zeanette Tiana Kaha; Orpa J Nubatonis; Helsina F Pello (Law Faculty, Nusa Cendana University, 2026)
Sumba Island in East Nusa Tenggara consists of four districts, one of which is Southwest Sumba which is inhabited by the Kodi, Wewewa, and Laura tribes. The Sumba community still strongly adheres to customs, especially in traditional marriages known as belis, namely the giving of dowry from the man's family to the woman's family. In the Kodi tribe, belis consists of horses, buffaloes, machetes, spears, and mamoli, with horses and buffaloes being the most valuable, while pigs are only complementary. This tradition is a symbol of respect and unification of two families. However, now, there has been a shift in values, where the amount of belis is more influenced by the level of education of women, reflecting a change from traditional values ​​to respect for education. The problems discussed in this journal are: (1) How are the Procedures for Buying in Traditional Marriages of the Kodi Tribe, Southwest Sumba Regency, NTT? and (2) What are the Obstacles or Constraints in the Implementation of Buying in Traditional Marriages of the Kodi Tribe, Southwest Sumba Regency, NTT? The research used is empirical legal research with data collection through interviews and literature studies. The results of the study show that Belis is a symbol of dignity and a form of respect for the woman's family, as well as the man's ability to fulfill the applicable customary responsibilities.